2006
DOI: 10.1002/sia.2145
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of cerium–europium co‐doped SiO2 phosphor prepared by a sol–gel process

Abstract: Ce3+ and Eu 3+ ions were simultaneously incorporated into a SiO 2 matrix by a sol-gel process, resulting in a phosphor that could be used in applications such as fluorescent lamps, solid state lasers, optical waveguides and field emission displays. Variation between blue and red emissions was obtained when co-doped SiO 2 : Ce,Eu powders with concentrations ranging from 0 to 5 mol% were exposed to ultraviolet light. An enhanced photoluminescence (PL) intensity from Ce 3+ , probably due to energy transfer from E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Another possibility for the increase in the CL intensity between 400 and 500 nm could be due to SiO 2 :Ce. Ntwaeaborwa et al [33] reported on the photoluminescence of SiO 2 :Ce, which resulted in a broad band emission spectrum between 400 and 500 nm (blue light) for 1 mol% concentration Ce. This broad band is due to the transitions in Ce 3+ and therefore could also possibly contribute to the increased CL intensity in Fig.…”
Section: Article In Pressmentioning
confidence: 98%
“…Another possibility for the increase in the CL intensity between 400 and 500 nm could be due to SiO 2 :Ce. Ntwaeaborwa et al [33] reported on the photoluminescence of SiO 2 :Ce, which resulted in a broad band emission spectrum between 400 and 500 nm (blue light) for 1 mol% concentration Ce. This broad band is due to the transitions in Ce 3+ and therefore could also possibly contribute to the increased CL intensity in Fig.…”
Section: Article In Pressmentioning
confidence: 98%
“…[14 -16] To compare the sol-gel as a chemical route for thin film production with physical deposition method, sputtering can also be utilized to fabricate high-quality thin layers due to its many advantages including flexibility and easy fabrication of diverse composite films with uniformly distributed metal particles and various metal-dielectric combinations. [17,18] In the sol-gel method, Ag particles are incorporated by dissolving silver salt in a precursor sol and Ag solute is generated in a silica matrix. On the other hand, cosputtering thin film deposition is followed by reduction using heat-treatment in a proper environment or UV irradiation producing Ag metallic particles.…”
Section: Introductionmentioning
confidence: 99%
“…As well known, the light emission from Ce 3+ is due to the transitions from 5d to 4f states, and the emission band of Ce 3+ is usually broad covering wavelengths from 350 to 600 nm [17,18]. In addition, an excitation spectrum of Er 3+ around the emission wavelength of 550 nm seems to range from 350 to 500 nm [12].…”
Section: Discussionmentioning
confidence: 99%